FEATURES AND NEW OPPORTUNITIES OF THE REPUBLIC OF CRIMEA TOURISM INDUSTRY - Burkaltseva, Diana; Apatova, Nataliya; Nalivaychenko, Ekaterina; Boychenko, Oleg; Yanovskaya, Anna; Betskov, Aleksandr; Kilyaskhanov, Hizri; Guk, Olga (Revista Inclusiones, 2019)
The aim of this work is to study the state of the tourism industry of the Republic of Crimea and determine its prospects. The tourism industry in the Republic of Crimea acts as a catalyst for the sustainable functioning and development of the regional socio-economic system, and allows us to search for factors and conditions that ensure the achievement of progressive socio-economic development indicators. The positive and negative impact of tourism on the economy of the region, regional tourism services, tourist flow on the Crimean peninsula, tax revenues to the budget of the Republic of Crimea from tourism activities are analyzed. Conclusions are made about the need to develop the tourism industry, create a tourism cluster in the Republic of Crimea and expand the range of tourism services.